Optimizing nitrogen and phosphorus application to improve soil organic carbon and alfalfa hay yield in alfalfa fields - Wei, Kongqin; Zhao, Junwei; Sun, Yanliang; López, Ignacio F.; Ma, Chunhui; Zhang, Qianbing (Frontiers in Plant Science, 2024)
Soil organic carbon (SOC) is the principal factor contributing to enhanced soil fertility and also functions as the major carbon sink within terrestrial ecosystems. Applying fertilizer is a crucial agricultural practice that enhances SOC and promotes crop yields. The objective of this study was to investigate the impact of nitrogen-phosphorus interactions on SOC and hay yield in alfalfa fields. A two-factor randomized group design was employed, with two nitrogen levels of 0 kg·ha-1 (N0) and 120 kg·ha-1 (N1) and four phosphorus levels of 0 kg·ha-1 (P0), 50 kg·ha-1 (P1), 100 kg·ha-1 (P2) and 150 kg·ha-1 (P3). The results showed that the nitrogen and phosphorus treatments increased SOC, easily oxidized organic carbon (EOC), dissolved organic carbon (DOC), particulate organic carbon (POC), microbial biomass carbon (MBC) and hay yield. The vertical distribution of SOC, EOC, DOC and POC under nitrogen and phosphorus treatments was highest in the 0–20 cm soil layer and tended to decrease with increasing depth of the soil layer. The MBC was highest in the 10–30 cm soil layer. DOC/SOC, MBC/SOC (excluding N0P1) and POC/SOC were all higher in the 0–40 cm soil layer compared to the N0P0, indicating that the nitrogen and phosphorus treatments effectively improved soil fertility, while EOC/SOC and DOC/SOC were both lower in the 40–60 cm soil layer than in the N0P0, indicating that the nitrogen and phosphorus treatments improved soil carbon sequestration potential. The soil layer between 0-30 cm exhibited the highest sensitivity index for MBC, whereas the soil layer between 30-60 cm had the highest sensitivity index for POC. This suggests that the indication for changes in SOC due to nitrogen and phosphorus treatment shifted from MBC to POC as the soil depth increased. Meanwhile, all fertilizers enhanced the soil Carbon management index (CMI) to varying degrees. Structural equation modeling shows that SOC is primarily impacted by POC and MBC. The comprehensive assessment indicated that the N1P2 was the optimal fertilizer application pattern. In summary, in agroecosystems, a recommended application rate of 120 kg·ha-1 for nitrogen and 100 kg·ha-1 for phosphorus is the most effective in increasing SOC content and alfalfa hay yield.